1990
DOI: 10.1128/aac.34.6.1285
|View full text |Cite
|
Sign up to set email alerts
|

Specific inhibitors of herpes simplex virus thymidine kinase diminish reactivation of latent virus from explanted murine ganglia

Abstract: Two specific inhibitors of herpes simplex virus thymidine kinase, N2-phenyl-2'-deoxyguanosine and N2-(m-trifluoromethylphenyl)guanine, were tested for their ability to inhibit the reactivation of virus from explant cultures of latently infected murine trigeminal ganglia. Both compounds significantly diminished the frequency of reactivation compared with that of untreated controls. We and others have recently shown that although thymidine kinase (TK)-negative HSV mutants fail to reactivate after explant culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…Some of these :functions are essential in adult neurons because of the absence of the cellular enzymatic counterparts. For instance, viral thymidine kinase, dispensable in peripheral replication of the virus, seems to be important for viral reactivation in nerve cells (Leib et al, 1990), where the cellular enzyme is not espressed. Recently we have demonstrated that uracil-DNA glycosylase, the enzyme which excises uracil residues from DNA, is also enzymatically undetectable in adult neurons Verri et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these :functions are essential in adult neurons because of the absence of the cellular enzymatic counterparts. For instance, viral thymidine kinase, dispensable in peripheral replication of the virus, seems to be important for viral reactivation in nerve cells (Leib et al, 1990), where the cellular enzyme is not espressed. Recently we have demonstrated that uracil-DNA glycosylase, the enzyme which excises uracil residues from DNA, is also enzymatically undetectable in adult neurons Verri et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…At the indicated times postexplant, ganglia were homogenized and plated exactly as for reactivation in vivo. Additional medium and serum conditions were tested in conjunction with the morphological and immunohistochemical studies including the conditions employed by several different groups (11,32,35), as well as the addition of nerve growth factor (44).…”
Section: Methodsmentioning
confidence: 99%
“…The modified nucleosides have a much higher affinity for HSV-1 thymidine kinase than for the cellular thymidine kinase, so that preferential phosphorylation in virus-infected cells occur. HSV-1 thymidine kinase could be a target for drugs which might prevent reactivation of HSV-1 when used prophylactically (Leib et al, 1990). …”
Section: Introductionmentioning
confidence: 99%